Chemoradiation followed by adjuvant durvalumab in stage III non–small cell lung cancer: Real‐world comparison of treatment outcomes to historical controls treated with chemoradiation alone. Issue 12 (11th May 2022) - Saad, Akram; Goldstein, Jeffrey; Appel, Sarit; Daher, Sameh; Urban, Damien; Onn, Amir; Gantz‐Sorotsky, Hadas; Lobachov, Anastasiya; Gottfried, Teodor; Spieler, Benjamin; Bar, Jair
Abstract: Objective: Compare outcomes in patients with stage III non–small cell lung cancer (NSCLC) treated with chemoradiation and adjuvant durvalumab to historical controls treated with chemoradiation alone. Methods: The records of patients with stage III NSCLC treated with definitive chemoradiation ± adjuvant durvalumab were reviewed retrospectively. Primary endpoints were progression free survival (PFS), overall survival (OS), and adverse events (AE). Results: Between September 2009 and September 2020, 215 patients were treated with concurrent chemoradiation (n = 144) or concurrent chemoradiation followed by adjuvant durvalumab ( n = 71). Compared to historical controls, durvalumab use was associated with improved PFS: median (27 months vs. 10 months, p < 0.0001), 1‐year (83.1% vs. 43.8, p < 0.0001); and improved OS; median (not reached vs. 24 months, p < 0.0001), 1‐year (85.9% vs. 81.9%, p < 0.0001). Multivariate analysis showed adjuvant durvalumab was associated with increased OS ( p = 0.005) and PFS ( p = 0.001). Within the durvalumab group, only clinical stage IIIA versus IIIB/C was associated with improved OS ( p = 0.049), but not PFS. There was no association between PFS or OS and Eastern Cooperative Oncology Group (ECOG) score, prior history of immune disease, programmed death‐ligand 1 (PD‐L1) receptor status, delay in starting durvalumab beyond 42 days, or development of an AE. During durvalumab treatment, 63 AE were reported in 52 patients with treatment discontinuation in 11. Pneumonitis was the most common AE reported ( n = 35, 49%). Most AE were grade 1–2 ( n = 57). Grade 3–4 AE were uncommon ( n = 6) and none were grade 5. Conclusion: Treatment with adjuvant durvalumab following chemoradiation was associated with improved PFS and OS compared to chemoradiation alone. Abstract : Treatment of stage III NSCLC with adjuvant durvalumab was associated with improved PFS and OS